THE EFFECT OF TEACHING ENGLISH USING DIGITAL STORYTELLING ON STUDENTS' WRITING SKILL AT THE SECOND GRADE OF SMP NEGERI 1 KAMPAR - Nadya Rosalina; Samsi Hasan (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
Based on this preliminary research, it was found that second grade students of SMP Negeri 1 Kampar got difficulties on their writing skill such as did not understanding how to start writing a story and cannot developing the ideas. This research aimed to know the effect of teaching English using digital storytelling on students’ writing skill especially in writing narrative text at the second grade of SMP Negeri 1 Kampar.The design of this research was a quasi-experimental. Therefore, this research used two class; control class and experimental class. The population of the research was second grade of SMP Negeri 1 Kampar. The object of this research was the effect of teaching English using digital storytelling on students’ writing skill. In this research, 59 students from 212 students were chooses as samples. To analyze the data, the researcher used independent sample t-test by using SPSS 20 version and effect size formula.Based on the data analysis, it was proved by finding of effect size formula was 0.13. It was categorized as moderate effect. It means that there was a significant effect of teaching English using digital storytelling on students’ writing skill at SMP Negeri 1 Kampar. Keywords: Effect, Digital Storytelling, Writing Skill, Narrative Text.